2019
DOI: 10.4191/kcers.2019.56.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Wet Foam Stability from Colloidal Suspension to Porous Ceramics: A Review

Abstract: Porous ceramics are promising materials for a number of functional and structural applications that include thermal insulation, filters, bio-scaffolds for tissue engineering, and preforms for composite fabrication. These applications take advantage of the special characteristics of porous ceramics, such as low thermal mass, low thermal conductivity, high surface area, controlled permeability, and low density. In this review, we emphasize the direct foaming method, a simple and versatile approach that allows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 135 publications
(206 reference statements)
0
12
0
Order By: Relevance
“…Screen-printing of composite materials relies on the preparation of an optimal paste [ 27 , 28 ]. A composite paste with PTC behavior was prepared by mechanically mixing commercially available PTC carbon ink (Ink−1M7511, 1-Material) and MWCNT (7311, 1-Material) powders.…”
Section: Methodsmentioning
confidence: 99%
“…Screen-printing of composite materials relies on the preparation of an optimal paste [ 27 , 28 ]. A composite paste with PTC behavior was prepared by mechanically mixing commercially available PTC carbon ink (Ink−1M7511, 1-Material) and MWCNT (7311, 1-Material) powders.…”
Section: Methodsmentioning
confidence: 99%
“…Han et al [5] have applied the Pickering-emulsion polymerization method using the ferromagnetic magnetite (Fe 3 O 4 ) nanoparticles, because it shows not only higher surfactant activity due to its amphiphilicity but also higher magnetic saturation value than that of Fe 2 O 3 [38][39][40][41]. PS (core)/ Fe 3 O 4 (shell) structured particles were synthesized by Pickeringemulsion polymerization method.…”
Section: Pickering-emulsion Polymerized Core− Shell-structured Polystyrene (Ps)/fe 3 Omentioning
confidence: 99%
“…Recent studies have shown that fabricating core-shell nanoparticles of a low-density polymeric material encapsulated by fine magnetic particles or introduction of a protective light polymer layer on the magnetic particles is a fairly efficient and promising method for lighter and therefore more stable suspensions [15][16][17]. In this regard, Fe 3 O 4 is being studied intensively due to its lower density than CI and relatively high magnetic properties as well as its excellent surface activities [6,18,41]. This is useful for fabricating core-shell particles using the Pickering-emulsion process since the solid Fe 3 O 4 particles can be used as a solid surfactant instead of conventional organic molecular surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Wet foams are extensively used, for example, in foods and cosmetics. As for material applications, wet foams are used to produce porous biomaterials [32] and ceramics, [33,34] and one of the most common applications of dry foams is found in the foam extrusion and foam injection molding of polymer composites. [35] Besides foam forming, foam coating is also being developed at the moment.…”
Section: Introductionmentioning
confidence: 99%